β-Catenin Interacts with MyoD and Regulates Its Transcription Activity - Kim, Chang-Hoon (American Society for Microbiology (ASM), 2008)
Wnt regulation of muscle development is thought to be mediated by the β-catenin-TCF/LEF-dependent canonical pathway. Here we demonstrate that β-catenin, not TCF/LEF, is required for muscle differentiation. We showed that β-catenin interacts directly with MyoD, a basic helix-loop-helix transcription factor essential for muscle differentiation and enhances its binding to E box elements and transcriptional activity. MyoD-mediated transactivation is inhibited in muscle cells when β-catenin is deficient or the interaction between MyoD and β-catenin is disrupted. These results demonstrate that β-catenin is necessary for MyoD function, identifying MyoD as an effector in the Wnt canonical pathway.